2011
DOI: 10.1161/hypertensionaha.111.171249
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Pressure and Hypertension With the Risk of Parkinson Disease

Abstract: Abstract-Cardiovascular risk factors, such as diabetes mellitus and central obesity, have been associated with Parkinson disease (PD), but data on blood pressure and PD are lacking. We sought to examine the association of blood pressure and hypertension with the risk of PD among men and women. This study consisted of 7 surveys Several population-based follow-up studies suggest that PD is associated with cardiovascular risk factors, such as diabetes mellitus and central obesity, 3,4 but the association with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
3
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 31 publications
7
92
3
3
Order By: Relevance
“…37 The biological mechanisms underlying such sex specificity remain unclear. Interestingly, several cardiovascular risk factors, such as hypercholesterolemia 38 and hypertension, 39 have been reported to be associated with increased risk of PD in women but not in men. This could play a part in the observed sex difference in the urate-PD relationship because higher urate concentrations are associated with these factors, which in turn might offset the potential neuroprotective effects of urate.…”
Section: Resultsmentioning
confidence: 99%
“…37 The biological mechanisms underlying such sex specificity remain unclear. Interestingly, several cardiovascular risk factors, such as hypercholesterolemia 38 and hypertension, 39 have been reported to be associated with increased risk of PD in women but not in men. This could play a part in the observed sex difference in the urate-PD relationship because higher urate concentrations are associated with these factors, which in turn might offset the potential neuroprotective effects of urate.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies [14,16,21,22] founded hypertension could reduce the risk of PD. However, some studies [23][24][25][26] founded hypertension could increase the risk of PD. Given the different effects, we carried out this meta-analysis to assess the relationship between hypertension and the risk of PD.…”
Section: Doi: 101159/000496977mentioning
confidence: 99%
“…3,4 Recent studies have suggested that PD is associated with certain vascular risk factors, such as diabetes 5,6 and hypertension. 7 Because these 2 conditions are also risk factors for AMI, these vascular comorbidities may confound the association between PD and AMI. One way of minimizing the potential confounding effects of comorbidities is to match various clinical characteristics between subjects with and without PD.…”
mentioning
confidence: 99%